2018
DOI: 10.1002/aic.16205
|View full text |Cite
|
Sign up to set email alerts
|

Shape dependence of resistance force exerted on an obstacle placed in a gravity‐driven granular silo flow

Abstract: Resistance force exerted on an obstacle in a gravity-driven slow granular silo flow is studied by experiments and numerical simulations. In a two-dimensional granular silo, an obstacle is placed just above the exit. Then, steady discharge flow is made and its flow rate can be controlled by the width of exit and the position of obstacle. During the discharge of particles, flow rate and resistance force exerting on the obstacle are measured. Using the obtained data, a dimensionless number characterizing the forc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…It has been found that the clogging of granular flow in silo can be significantly reduced or even suppressed by putting an obstacle at one to two times outlet size above the outlet 52,53 . For stable silo discharge, installing an obstacle at a proper position of the bottom converging zone can even lead to a higher flow rate than the case without obstacle 14,26–28 . Based on the simulation results presented here, it can be reasonably deduced that the presence of obstacle can modify the fluctuating characteristics of flow field.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It has been found that the clogging of granular flow in silo can be significantly reduced or even suppressed by putting an obstacle at one to two times outlet size above the outlet 52,53 . For stable silo discharge, installing an obstacle at a proper position of the bottom converging zone can even lead to a higher flow rate than the case without obstacle 14,26–28 . Based on the simulation results presented here, it can be reasonably deduced that the presence of obstacle can modify the fluctuating characteristics of flow field.…”
Section: Discussionmentioning
confidence: 60%
“…Another reason triggering this research work is the hypothesis that the discharge of granular materials from silo seems to be controlled by the flow of particles in the vicinity of outlet. It has been found experimentally and numerically that the presence of obstacle at a proper position of the bottom converging zone can lead to higher flow rate than the case without obstacle 26–28 . Explanations to this counterintuitive phenomenon are generally based on contact dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Granular flow, which enables material storage, material transfer, and on‐stream catalyst replacement (OCR), extensively exists in chemical processes, such as silo discharge, pneumatic conveying, and processes involved in moving bed reactors 1–3 . Accurate understanding of complex dynamic behaviors of granular flow is critical for the design and optimum of these processes, and numerous investigations have been carried out on this 4,5 . In a macroscopic view, Jenike et al 6 for the first time divided the particle flow patterns in silo discharging into two types including mass flow and funnel flow, and the classification and definition have been widely accepted and used in related research areas since then.…”
Section: Introductionmentioning
confidence: 99%
“…Saat mainan terjun payung dilepaskan, gravitasi akan mulai bekerja pada mainan tersebut. Gaya yang bekerja adalah berat mainan yang ditentukan oleh massa mainan dan percepatan gravitasi (Jing, 2021;Katsuragi, 2018;Shigorina, 2019;Wang, 2018Wang, , 2020. Gravitasi memiliki percepatan sebesar 9,8 m/s^2 di Bumi.…”
Section: Pendahuluanunclassified